Eunuchs of Yakutsk Region on Pages of Regional Periodicals in Late 19th — Early 20th Centuries - V. S. Matyushchenko; R. A. Yakusheva (Научный диалог)
The materials of pre-revolutionary periodicals of Yakutia of the late 19th — early 20th centuries, containing information about the life of sectarian Eunuchs in the region are analyzed in the article. The reference to these sources is necessary in order to reconstruct the history of the scavenger in connection with the current interest in modern science in the publications of the regional print press, which were not previously taken into account by the researchers. The novelty of the research lies in the replenishment of knowledge of the history of skopstvo in Yakutia due to the introduction of new historical sources into scientific circulation. An analysis of the materials of the Yakut press allows us to conclude that the role of Eunuchs in the development of arable and truck farming in Yakutia remained an urgent topic years after their release from exile. The authors pay special attention to the coverage of the everyday side of skopic life on the pages of periodicals. The similarity of news stories about sectarians form a stable idea of the relationship of Eunuchs with the local population, lifestyle and models of behavior in the Yakut reality of the late 19th — 20th centuries.